1997
DOI: 10.1042/bj3220845
|View full text |Cite
|
Sign up to set email alerts
|

New α-l-arabinofuranosidase produced by Streptomyces lividans: cloning and DNA sequence of the abfB gene and characterization of the enzyme

Abstract: A fully secreted alpha-l-arabinofuranosidase was cloned from the homologous expression system of Streptomyces lividans. The gene, located upstream adjacent to the previously described xylanase A gene, was sequenced. It is divergently transcribed from the xlnA gene and the two genes are separated by an intercistronic region of 391nt which contains a palindromic AT-rich sequence. The deduced amino acid sequence of the protein shows that the enzyme contains a distinct catalytic domain which is linked to a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 33 publications
2
37
1
1
Order By: Relevance
“…HPAEC analyses confirmed that L-arabinose was the only product released from debranched ␣-1,5-linked arabinan (data not shown), and kinetic analyses determined that the k cat values for arabinan and pNP-␣-L-arabinofuranoside were 30 and 140 times lower than the apparent k cat value for WAX-HV, respectively (Tables 2 and 3). The clear preference of SthAbf62A for polymeric substrates (i.e., arabinoxylan) is consistent with other GH62 members (32)(33)(34)(35)(36)38) and continues to distinguish GH62 enzymes from arabinofuranosidases identified in other GH families. Regioselectivity of SthAbf62A.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…HPAEC analyses confirmed that L-arabinose was the only product released from debranched ␣-1,5-linked arabinan (data not shown), and kinetic analyses determined that the k cat values for arabinan and pNP-␣-L-arabinofuranoside were 30 and 140 times lower than the apparent k cat value for WAX-HV, respectively (Tables 2 and 3). The clear preference of SthAbf62A for polymeric substrates (i.e., arabinoxylan) is consistent with other GH62 members (32)(33)(34)(35)(36)38) and continues to distinguish GH62 enzymes from arabinofuranosidases identified in other GH families. Regioselectivity of SthAbf62A.…”
Section: Resultssupporting
confidence: 51%
“…1D). In contrast, PchAraf62, SliAraf62, and ScAraf62A lost all activity after 60 min at 60°C (33,34,36), and the optimal reaction temperatures for UmAbf62A and PaAbf62A are 37°C and 55°C, respectively (32,53).…”
Section: Resultsmentioning
confidence: 99%
“…Maximal enzyme activity was detected at pH 5.5 at 35°C. ScAraf62A was stable between pH 7.0 and 9.0 at 35°C for 1 h. It was also stable up to 30°C at pH 5.5 for 1 h. The optimum temperature for ScAraf62A was lower than that for AbfB ␣-Larabinofuranosidase from S. lividans (55°C) (46). However, these could not be simply compared because the experimental conditions, such as the substrates used, were different.…”
Section: Scaraf62amentioning
confidence: 91%
“…The deduced amino acid sequence was compared with sequences in the protein database using a BLAST search (National Center for Biotechnology Information, www.ncbi.nlm.nih.gov). The ScAraf62A (Sco5932) sequence resembled that of AbfB, an ␣-L-arabinofuranosidase from S. lividans (46), and the amino acid similarity was 97% (data not shown). To express ScAraf62A, the DNA fragment encoding the full-length protein was cloned.…”
Section: Scaraf62amentioning
confidence: 99%
“…Subfamily GH43_7 has yet to have a member characterized, but we observed that all GH43_7 proteins also harbor a CBM13 module. A CBM13-containing ␣-L-arabinofuranosidase (AbfB) has been characterized for the soil actinomycete Streptomyces lividans (32) and has demonstrated xylan-binding functionality. This cooccurrence hints toward ␤-D-xylosidase (EC 3.2.1.37) and ␣-L-arabinofuranosidase (EC 3.2.1.55) activities, as seen in the subfamilies above associated with CBM6 xylan-binding domains.…”
Section: Resultsmentioning
confidence: 99%